ANALISIS STRATEGI DAN PENDEKATAN PEMBELAJARAN DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sabrun Jamil; Anis Nirmala Patmawati; Fathir Rahman Muzakhy; Rido Agustian; Silvia Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze learning strategies and approaches that can enhance the effectiveness of Islamic Religious Education (IRE) learning. A qualitative approach with a library research method was employed. Data were collected by reviewing relevant scholarly sources, including books, journal articles, conference proceedings, and other academic documents, and were subsequently analyzed using content analysis. The findings indicate that active, contextual, problem-based, project-based, and engaging learning strategies can encourage greater student involvement in the learning process. In addition, contextual, humanistic, scientific, inquiry-based, experiential, and rational approaches can contribute to improving students’ learning motivation, understanding of the subject matter, and critical thinking skills. However, the effectiveness of IRE learning is not determined solely by the strategies and approaches employed. It is also influenced by teachers’ competencies, the availability of educational facilities and resources, the integration of technology, and support from both school and family environments. Therefore, teachers need to carefully select and combine appropriate learning strategies and approaches based on learning objectives, the characteristics of the subject matter, and students’ needs. Such considerations are essential for creating effective and meaningful IRE learning experiences that contribute to students’ character development.